The Love Affairs of a Bibliomaniac - Field, Eugene, 1850-1895 (Salt Lake City, UT : Project Gutenberg, 1996)
"The Love Affairs of a Bibliomaniac" by Eugene Field is a collection of autobiographical essays written during the late 19th century. This work showcases Field's passion for book collecting, exploring both the joys and the quirks that come with bibliomania. The narrative is framed around the experiences of the main character, an avid book lover, who reflects on his life, the books he cherishes, and the significant moments intertwined with his literary pursuits. At the start of the book, the author introduces a humorous and introspective character steeped in nostalgia and affection for his earliest encounters with books. He recalls the charm of finding love in the pages of an old "New England Primer" and his literary journey through childhood. The opening portion also shares the author's affection for notable figures from his past, like Captivity Waite, and sets an overall tone of playful reverie. As he examines his relationships with various books, the character's reflections shed light on the transformative power of literature and its enduring place in one's life, blending humor with heartfelt sentiment. (This is an automatically generated summary.)
My first love -- The birth of a new passion -- The luxury of reading in bed -- The mania of collecting seizes me -- Baldness and intellectuality -- My romance with Fiammetta -- The delights of fender-fishing -- Ballads and their makers -- Booksellers and printers, old and new -- When Fanchonette bewitched me -- Diagnosis of the Bacillus Librorum -- The pleasures of extra-illustration -- On the odors which my books exhale -- Elzevirs and divers other matters -- A book that brings solace and cheer -- The malady called Catalogitis -- The Napoleonic Renaissance -- My workshop and others -- Our debt to monkish men.
Release date is 1996-02-01
Produced by Charles Keller
Keywords: Book collecting